2020
DOI: 10.3390/antibiotics9120862
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Resistance and Genomic Characterization of OXA-48- and CTX-M-15-Co-Producing Hypervirulent Klebsiella pneumoniae ST23 Recovered from Nosocomial Outbreak

Abstract: Multidrug resistance (MDR) and hypervirulence (hv) have been long considered distinct evolutionary traits for Klebsiella pneumoniae (Kp), a versatile human pathogen. The recent emergence of Kp strains combining these traits poses a serious global threat. In this article, we describe the phenotypic and genomic characteristics of an MDR hvKp isolate, MAR14-456, representative of a nosocomial outbreak in Moscow, Russia, that was recovered from a postoperative wound in a patient who later developed multiple absces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
25
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 32 publications
3
25
0
2
Order By: Relevance
“…Shaidulina et al used Illumina MiSeq and ONT MinION systems and succeeded in localizing the virulence genes and bla OXA-48 on different plasmids. To the best of our knowledge, no reports of CR-hvKp isolates with confirmed hybrid plasmids coharboring genes of carbapenemases and virulence genes have been published in Russia so far [11]. In the present study, we aimed to describe the emergence of Kpn isolates of different STs (ST15, ST147, ST395, and ST874) with hybrid plasmids co-harboring virulence genes and bla NDM in the hospitals in St. Petersburg.…”
Section: Introductionmentioning
confidence: 93%
“…Shaidulina et al used Illumina MiSeq and ONT MinION systems and succeeded in localizing the virulence genes and bla OXA-48 on different plasmids. To the best of our knowledge, no reports of CR-hvKp isolates with confirmed hybrid plasmids coharboring genes of carbapenemases and virulence genes have been published in Russia so far [11]. In the present study, we aimed to describe the emergence of Kpn isolates of different STs (ST15, ST147, ST395, and ST874) with hybrid plasmids co-harboring virulence genes and bla NDM in the hospitals in St. Petersburg.…”
Section: Introductionmentioning
confidence: 93%
“…However, varying rates of resistance to all of them have been reported, thus different antibiotics are continuously being tested. Treatment of OXA-48 CRE with ceftazidime-avibactam could be effective according to a study conducted in Italy [ 105 ], which is consistent with the resistance profile of an OXA-48 CRE outbreak in Russia [ 106 ]. A study performed in Australia also reported effectiveness of other avibactam combinations (imipenem-avibactam or aztreonam-avibactam), suggesting that avibactam may be the most potent β-lactamase inhibitor [ 107 ].…”
Section: Treatmentmentioning
confidence: 55%
“…Although the authors stated that combined therapy is more effective, successful outcomes were observed in 70% of the patients treated with ceftazidime-avibactam in monotherapy. Carbapenem in combination with amikacin or colistin may be useful in certain cases, but recent reports of resistance are concerning [ 106 ].…”
Section: Treatmentmentioning
confidence: 99%
“…Although not as notorious as K. pneumoniae , the other CPB described in this study form part of a group of multidrug-resistant microorganisms that pose a major public health threat [ 34 ] and show increased diversity over time, as reported in a Portuguese study [ 4 ]. The frequency of their detection is rising among colonized and infected hospital patients, despite the implementation of infection prevention and control measures and routine colonization screenings [ 4 ].…”
Section: Discussionmentioning
confidence: 96%